2015
DOI: 10.1038/bmt.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

Chronic GvHD-associated serositis and pericarditis

Abstract: Serositis is a rare manifestation of chronic GvHD (cGvHD). No risk factors or laboratory changes associated with this syndrome have been recognized to date, and outcomes have not been described in a large series. We searched our institutional database for patients undergoing allogeneic hematopoietic cell transplant identified as having serositis or pericarditis. Laboratory studies from prior to diagnosis, at diagnosis and post diagnosis of serositis, as well as outcomes from invasive procedures were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…Serositis type chronic GVHD, and BOOP were accountable for the second peak. The incidence of serositis type GVHD in our study was 1.23% which is close to 1.8% and 0.8% as reported by Leonard et al and Norkin et al, respectively . Both these studies primarily intended to investigate pericardial effusion or pericarditis as a manifestation of serositis, while our study was focused on exploring pleural effusion.…”
Section: Discussionsupporting
confidence: 83%
“…Serositis type chronic GVHD, and BOOP were accountable for the second peak. The incidence of serositis type GVHD in our study was 1.23% which is close to 1.8% and 0.8% as reported by Leonard et al and Norkin et al, respectively . Both these studies primarily intended to investigate pericardial effusion or pericarditis as a manifestation of serositis, while our study was focused on exploring pleural effusion.…”
Section: Discussionsupporting
confidence: 83%
“…Serositis is recognized as inflammation of any of the serosal linings of the body. In a non-transplant setting, serosal inflammation can be caused by a variety of factors including infection, autoimmune disease, and malignant disease [2]. In the setting of HSCT, serositis is a well-recognized but rare manifestation of cGVHD-associated conditions [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of HSCT, serositis is a well-recognized but rare manifestation of cGVHD-associated conditions [5]. Evidence regarding serositis after allogeneic HSCT is limited to case reports and a small case series because of its low frequency, with an incidence of 1–2% [2, 6, 7]. Seber et al reported an association between unexplained effusions and acute and cGVHD [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations